THE USE OF VIDEO IN TEACHING ENGLISH SPEAKING (A Quasi-Experimental Research in Senior High School in Sukabumi) - Muchamad Iqbal Ali Akbar Hakim (Journal of English and Education, 2016)
Speaking skill is one of the four language skills that should be mastered by, in this case, students to be able to communicate with their surroundings. However, there are some difficulties for teachers to ask or to stimulate students to speak in English. It is very important for English teachers to use interesting media especially the ones that give context to the students in the learning process such as videos. This study aims to find out the effectiveness of video to improve students’ speaking ability and to investigate the most improved aspect of speaking by video. The study was conducted in one of Senior High Schools in Sukabumi. A quasi-experimental design was employed for this study. The study involved two classes of eleventh grader which were divided into two groups; experimental group and control group. Data were collected through pretest and posttest. The data were analyzed by using Statistical Product and Service Solutions (SPSS) 18 for Windows. The calculation result of independent t-test on posttest scores showed that the significance value was lower than 0.05 (0.000 0.05) which means the video treatment had improved the students’ speaking ability. In line with the result, the calculation of effect size also showed that video improved the students’ speaking ability by the score of effect size in large level (0.697). Furthermore, the use of video in teaching speaking also solved one of the hardest aspects of speaking for students: pronunciation. It is showed by the result between pretest score means and posttest score means from each aspect and pronunciation had biggest improvement with 0.67 difference from pretest to posttest. For that reasons it is highly recommended that teachers use video as media to teach speaking in classroom.